PERGESERAN PENGGUNAAN KATA SAPAAN OLEH GENERASI MILENIAL BANJAR DI KOTA BANJARBARU - Eka Suryatin (Prasasti: Journal of Linguistics, 2020)
This study was designed to describe the change in greeting words used by the Millennial Floods in Banjarbaru City and the factors that influence them. This study used descriptive qualitative method. Data collection by refer to the method. Data analysis was performed using the matching method and the advanced technique of the Determination of the Determination Element (PUP) technique. The data used consists of greetings used by the millennial generation of Banjar in Banjarbaru. The research data source consisted of utterances delivered by the Banjar millennial generation in Banjarbaru. The results showed the greeting words used by the Banjar millennial generation in Banjarbaru City increased rotation. Occurs when family runs, kinship, and intimacy. The most shifted form of greeting words occurs in the realm of the family, namely the immediate family. The displacement language used by the millennial flood generation, namely Indonesian and languages (Arabic and English) even has the Banjar language itself. Factors that influence change, namely the existence of urbanization, the progress of science and technology, the language of prestige, and generation over.